Kinetics and energetic analysis of the slow dispersive electron transfer from nano-TiO2 to O2 by in situ diffusion reflectance and Laplace transform. Issue 35 (1st September 2021) - Wu, Zhizhou; Li, Liuyang; Zhou, Xuedong; Zhao, Xiujian; Liu, Baoshun
Abstract : In situ diffusion reflectances reveal the trapping-filling effect in the electron transfer from TiO2 to O2 and Laplace transform was developed to derive the broadened apparent barrier energy distribution. Abstract : Electron transfer to O2 is a universally existing process for the physiochemistry of many materials. Electron transfer to O2 is also an inevitable process for photocatalytic reactions over TiO2 and other materials. In the present research, a diffusion reflectance system was developed to measure in situ optical diffusion reflectances caused by photoinduced electrons in nano-TiO2 under a steady light illumination; in situ absorption decays can be obtained to study the electron transfer from their trapped states to O2 . It is seen that the kinetics of electron transfer to O2 is persistent and dispersive; this lasts for several minutes and approximately agrees with a stretched exponential kinetics. The result implies that variable apparent energy barriers ( E i s) are involved in the electron transfer. The effects of O2 amount, light intensity, and temperature are studied and the results mean the trap-filling effect should be involved in the electron transfer to O2 . A Laplace transform is used to derive the E i distributions. It is found that the E i dispersion shape almost does not change; this indicates that the physical reason causing the E i dispersion is the same for different experimental conditions and possibly comes from the trap-filling effect. It is shown that the slow kinetics of the electron transfer is also dependent on the slow rate for an electron transferring from a trap to O2, in additional to the trapping-filling effect. The results indicate that the photocatalytic activity can be increased through a modulation in trap distribution.